O062 Acquired carotid-jugular fistulas following carotid endarterectomy: a narrative review. (22nd July 2022) - Narroway, H; Bourke, B; Tchen, A
Abstract: Introduction: Acquired arterio-venous fistulas (AVF) involving the carotid artery are most commonly the result of trauma and catheterisation of the neck vessels. Left untreated, carotid-jugular fistulas (CJF) may precipitate ischaemic neurological symptoms due to thromboembolism or shunting of blood through the AVF. Methods: A literature review was performed to determine the incidence and outcomes of acquired carotid-jugular AVFs following carotid endarterectomy (CEA). Electronic searches were performed using three databases, PubMed, EMBASE, and Google Scholar. Results: Three case studies met inclusion criteria for analysis. The first case occurred 4-months following a left CEA. CT-angiography and duplex ultrasound identified a pseudoaneurysm arising from the proximal internal carotid artery. A CJF was identified on re-intervention and carotid ligation was performed following unsuccessful attempts to repair the defect. The patient has ongoing mild dysphonia with no other complications at 18 months follow-up. The second case occurred 6 years following right CEA. Catheter angiography revealed an AVF between the right external carotid artery (ECA) and internal jugular vein, treated with coil embolization. The patient made complete neurological recovery and had no further complications at 2 years follow-up. The third case occurred 4 years following right CEA. Catheter angiography identified fistulisation between the lingual branch of the right ECA and right retromandibular vein, treated with transarterial particle embolization. The patient made a complete neurological recovery. Conclusion: Carotid-jugular AVFs are rare following CEA. This review proposes that carotid-jugular AVFs may be amenable to both open and endovascular intervention with durable outcomes. Proceduralists should be cognisant of this complication. Take-home message: Carotid-jugular arteriovenous fistulas are rare following carotid endarterectomy and may be amenable to both open and endovascular intervention with durable outcomes.